2014
DOI: 10.1177/0004563214534832
|View full text |Cite
|
Sign up to set email alerts
|

A simple electronic alert for acute kidney injury

Abstract: Background: Acute kidney injury (AKI) is frequently under-recognized and contributes to poor outcomes. Electronic alerts (e-alerts) to highlight AKI based on changes in serum creatinine may facilitate earlier recognition and treatment, and sophisticated algorithms for AKI detection have been proposed or implemented elsewhere. However, many laboratories currently lack the resources or capability to replicate these systems. Methods: A real-time automated delta check e-alert flags a 50% increase in creatinine to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…Manual chart review by two physicians is a well-recognized reference standard for kidney injury outcomes, and the 91 % agreement between the two initial reviewers in our study was similar to that observed in previous AKI studies [28, 31]. Including all ICU admissions allowed examination of performance characteristics over a wide spectrum of underlying illness, including patients with CKD (for whom risk of AKI is high but assessment of baseline creatinine may be challenging) and patients receiving RRT prior to admission (who remain at risk for the in-hospital mortality component of MAKE).…”
Section: Discussionsupporting
confidence: 87%
“…Manual chart review by two physicians is a well-recognized reference standard for kidney injury outcomes, and the 91 % agreement between the two initial reviewers in our study was similar to that observed in previous AKI studies [28, 31]. Including all ICU admissions allowed examination of performance characteristics over a wide spectrum of underlying illness, including patients with CKD (for whom risk of AKI is high but assessment of baseline creatinine may be challenging) and patients receiving RRT prior to admission (who remain at risk for the in-hospital mortality component of MAKE).…”
Section: Discussionsupporting
confidence: 87%
“…APCI and APPI), or with other instrumentation or chromatographic conditions. Recently, an article has been published leading to a similar conclusion of overestimation of the 3-epi-25(OH)D 3 concentration from increased ionisation using ESI-LC-MS/MS [24]. These authors showed that signal enhancement was dependent on mobile phase composition, with increasing signal enhancement at higher methanol concentrations.…”
Section: Methods Comparisonmentioning
confidence: 89%
“…For instance, when the patient was using a SSRI and the sodium level was 129 mmol/l, only marginally low, the CDSS would alert the physician while during the grand round this sodium level might have been noticed but did not immediately alarm the physicians. Perhaps a fixed cut-off value is not always significant, but a percentage change in a certain value may be more useful in clinical practice, [23]. On the down-side, relying solely on percent changes of laboratory values may only detect events at a late stage.…”
Section: Improving the Cdssmentioning
confidence: 99%